Pemanfaatan Miang Bambu Betung (Dendrocalamusasper) Sebagai RacunTikus Utilization of “Miang”Dendrocalamus asper (bambu betung) as Rat Poison - Frans Hutasoit; Yunus Afifuddin; Ridwanti Batubara (Peronema Forestry Science Journal, 2015)
The used chemically rodenticides to control  rodent pest can have a negatively impact on the environment and human life. Utilization of eco-friendly  natural materials  such as “miang “ Dendrocalamus asper(bambu betung)   is one kind of solution that is expected to be used as an alternative material to control rodent pest. This research purposed to determine the effectivenes of “miang” Dendrocalamus asper(Bambu Betung) against  mortality of white rats (Rattus novergicus, L.) by used the baits  mixed  with bamboo miang betung at various concentrations (0%, 5%, 10%, 15%, 20%) on rodent  morbidity and mortality rate . The results of this research  indicates that  mixing the bamboo miang into  baits,  effect on  mortality of rodent. The concentration of 10% of the measure is the most  effectivebecause has killed 100%  of  rats. This research indicates that miang bamboo high  toxicity and  very  potential to be develope as an eco-friendly plant-based rodenticides. Keywords: Dendrocalamus asper,miang, rat, rodenticides, mortality